Provider Barriers and Facilitators of Breast Cancer Guideline‐Concordant Therapy Delivery in Botswana: A Consolidated Framework for Implementation Research Analysis. (2nd September 2021) - Ralefala, Tlotlo; Mokokwe, Lebogang; Jammalamadugu, Swetha; Legobere, Dumelang; Motlhwa, Warona S.; Oyekunle, Anthony A.; Grover, Surbhi; Barg, Frances K.; Shulman, Lawrence N.; Martei, Yehoda M.
Abstract: Introduction: Systemic treatment for breast cancer in sub‐Saharan Africa (SSA) is cost effective. However, there are limited real‐world data on the translation of breast cancer treatment guidelines into clinical practice in SSA. The study aimed to identify provider factors associated with adherence to breast cancer guideline‐concordant care at Princess Marina Hospital (PMH) in Botswana. Materials and Methods: The Consolidated Framework for Implementation Research was used to conduct one‐on‐one semistructured interviews with breast cancer providers at PMH. Purposive sampling was used, and sample size was determined by thematic saturation. Transcribed interviews were double‐coded and analyzed in NVivo using an integrated analysis approach. Results: Forty‐one providers across eight departments were interviewed. There were variations in breast cancer guidelines used. Facilitators included a strong tension for change and a government‐funded comprehensive cancer care plan. Common provider and health system barriers were lack of available resources, staff shortages and poor skills retention, lack of relative priority compared with HIV/AIDS, suboptimal interdepartmental communication, and lack of a clearly defined national cancer control policy. Community‐level barriers included accessibility and associated transportation costs. Participants recommended the formal implementation of future guidelines that involved key stakeholders in all phases of planning and implementation, strategic government buy‐in, expansion of multidisciplinary tumor boards, leveraging nongovernmental and academic partnerships, and setting up monitoring, evaluation, and feedback processes. Discussion: The study identified complex, multilevel factors affecting breast cancer treatment delivery in Botswana. These results and recommendations will inform strategies to overcome specific barriers in order to promote standardized breast cancer care delivery and improve survival outcomes. Implications for Practice: To address the increasing cancer burden in low‐ and middle‐income countries, resource‐stratified guidelines have been developed by multiple international organizations to promote high‐quality guideline‐concordant care. However, these guidelines still require adaptation in order to be successfully translated into clinical practice in the countries where they are intended to be used. This study highlights a systematic approach of evaluating important contextual factors associated with the successful adaptation and implementation of resource‐stratified guidelines in sub‐Saharan Africa. In Botswana, there is a critical need for local stakeholder input to inform country‐level and facility‐level resources, cancer care accessibility, and community‐level barriers and facilitators. Abstract : To address an increasing mortality burden, resource‐stratified guidelines have been developed to ensure that breast cancer care is matched to specific resources in low‐ and middle‐income countries. This article identifies facilitators and barriers to the use of breast cancer guidelines by oncology providers at Princess Marina Hospital in Botswana using the Consolidated Framework for Implementation Research (CFIR).